Introduction-The Family and Medical Leave Act of 1993: Ten Years of Experience - Pauline T. Kim (Washington University Journal of Law & Policy, 2004)
Which of the FMLA’s articulated purposes one views as central will critically affect one’s assessment of the statute. The contributions to this Symposium differ from one another not only in the methodologies they employ to assess the impact of the FMLA, but also in their assumptions about the primary goal of the FMLA. From these varying perspectives, they offer differing responses to such questions as: Has the law met expectations? In what ways has it fallen short and why? And what further needs to be done to meet the goals the FMLA was intended to advance? Law professors Joanna Grossman and Michael Selmi each evaluate the FMLA in terms of its contribution—or lack thereof—to gender equality in the workplace. From this perspective, the law appears mostly a symbolic gesture, one short on substance and of little practical utility in promoting actual equality in the workplace. Prior to passage of the FMLA, a patchwork of state laws and voluntary employer initiatives determined the availability and terms of leave for the individual worker. In this world, women typically took leave when they had a child; men rarely did so. Although the FMLA formally includes men its leave protections, the basic pattern of leave-taking for family care has hardly changed in ten years. To the extent, then, that the FMLA was intended to combat gender stereotypes and reduce discrimination against women, it has not accomplished these goals.
Keywords: Parental leave; Parenting; Sex discrimination in employment